Local Wisdom-based Dance Learning: Teaching Characters to Children through Movements - Rosala, Dedi; Budiman, Agus (Universitas Pendidikan Indonesia, 2020)
The character education implementation in every school becomes a program of national education system policy in Indonesia. Its orientation is more focused on advancing national character development based on local wisdom and unique culture in Indonesia. The authority of the Indonesian education system policy program in strengthening character education covers religiousness, nationalism, independency, mutual cooperation, and integrity with the development of local wisdom-based learning materials. The purpose of this research is to discover the process of dance learning implementation in students’ character education development. This research employs quantitative with descriptive statistics data analysis. The data were collected through an observation of 22 primary school students during a dance learning process and in-depth interviews to two dance teachers to obtain data regarding local wisdom-based dance learning implementation to develop students’ characters. The findings show that character education developed in local wisdom-based dance learning can be done through various learning activities such as appreciation and introduction of traditional dance materials, instilling values, independent and group study to build independency and mutual cooperation, and familiarize students to pray before and after learning. These are to plant local wisdom values through dance movement learning.